Does reserve accumulation lead to higher currency-risk taking in the corporate sector? Firm-level evidence for Latin America - Rajeswari Sengupta (University of California, Santa Cruz Institute for International Economics (SCIIE), 2010)
I explore an empirically robust but previously undocumented association between the foreign exchange reserves accumulated by central banks of emerging market economies and dollar-denominated debt held in the balance sheets of non financial sector firms. Borrowing in dollars can have damaging effects on corporate balance sheets in the event of exchange rate depreciation. However, firms may discount such risk because of the implicit insurance provided by the central bank's ex-ante reserve accumulation: in the event of a currency depreciation, firms may expect the central bank to stabilize the exchange rate using its stock of reserves. Using a novel firm-level balance sheet database, I investigate this possibility for close to 1500 firms in six of the largest Latin American economies, Argentina, Brazil, Chile, Colombia, Mexico and Peru. Results suggest that over the sample period, 1995-2007, an increase in the level of reserves is statistically and economically associated with an increase in the dollar borrowing of non financial sector firms of these economies. This could hint at a possible paradox: a higher level of reserves need not necessarily signify an economy that is more resilient to shocks. While reserve accumulation enables governments to weather macroeconomic risks arising from sudden stops in international capital flows, it can also increase the vulnerability of the corporate sector to currency risks by distorting incentives. Thus central banks, while formulating their foreign exchange intervention policies, may need to take into consideration the impact of the resultant reserve stockpiling on the private sector.
Keywords: F3; F4; 330; foreign exchange reserves; foreign currency denominated debt; corporate risk-taking; currency depreciation